Bacterial pathogenomics - Pallen, Mark J.; Nelson, Karen E.; Preston, Gail M. (Monograph, ASM Press., 2007)
This landmark volume details progress in the fast-changing world of bacterial genomics and it includes contributions from a team of over forty world-renowned authors.